HUBUNGAN KUALITAS TIDUR DENGAN GLUKOSA DARAH PADA PASIEN DIABETES MELLITUS TIPE II - Sutiswa, Shandra Isasi; Gustini, Gustini; Yoyoh, Imas; Ali, Mohammad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Diabetes mellitus has become an increasingly serious health problem, with the incidence rate continuing to increase significantly. The results of a preliminary study conducted by researchers in May 2023 on 10 patients with type II diabetes mellitus (DM type II) who were undergoing treatment at Prima Hospital showed significant findings. Of the 10 patients involved in the study, 8 reported frequent difficulty sleeping at night and feeling tired during the day. The purpose of the study was to determine the relationship between sleep quality and blood glucose in patients with type II diabetes mellitus. The research design used in this study was cross sectional. The research was conducted in July 2023 at Prima Hospital. The population was all type II DM patients who were recorded as many as 31 people from July to August 2023, with details of the number of type II DM patients who visited the poly in July to August 2023, totaling 31 people as well as the research sample. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed there was a relationship between sleep quality (p value: 0.003) with blood glucose levels. It is recommended that the hospital can improve services, especially in the field of nursing care for type II DM patients.Keywords: Diabetes, Blood Glucose Levels, Sleep Quality.